Self‐Aligned Trapping and Detecting Molecules Using a Plasmonic Tweezer with an Integrated Electrostatic Cell. Issue 5 (9th February 2017) - Yan, Zhongbo; Xia, Ming; Zhang, Pei; Xie, Ya‐Hong
Abstract : Surface plasmonic tweezers and electrostatic forces can be employed as complementary methods for trapping and detecting molecules with high sensitivity and selectivity. The hotspots—localized regions of highly concentrated electromagnetic fields with large gradients—give rise to both the plasmonic tweezer effect and the surface‐enhanced Raman scattering (SERS) effect. So naturally, combining plasmonic tweezers and SERS makes for an ideal label‐free method for trapping and detecting molecules. Here, the trapping effect of the plasmonic tweezer is demonstrated by using the unique graphene–Au pyramid hybrid platform. While very powerful, the force associated with plasmonic tweezers is a short‐range effect (<50 nm from the spot of peak intensity). The electrostatic force, on the other hand, has long‐range interaction extending to beyond micrometers, which can guide molecules toward the hotspots. The authors present experimental evidence showing the combination of plasmonic tweezers and electrostatic forces by using an integrated electrostatic cell. Using the combined platform, trapping of single molecules in dilute solution is observed. These observations indicate a new approach for enhancing SERS sensitivity. It also offers a realistic possibility for precisely positional control of biomolecules, allowing the study of the properties of single biomolecules. Abstract : A self‐aligned trapping method of single molecules is demonstrated by combining a plasmonic tweezer and electrostatic force. A unique graphene–Au pyramid platform is employed to induce plasmonic tweezer effect and used for label‐free detection of the molecules. This method offers a realistic possibility for precisely positional control of single biomolecules, and allows the study of their properties.